2006
DOI: 10.1111/j.1468-3083.2006.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life before and 6 weeks after treatment in a dermatological outpatient treatment unit

Abstract: Dermatological diseases have an important influence on patients' quality of life. Attending an outpatient treatment unit was in this series of cases associated with improved quality of life as measured with the DLQI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
(36 reference statements)
1
17
0
Order By: Relevance
“…An explanation for this may be that the SQoL in men was not severely enough affected, so there was less room for improvement. The fact that clinical improvement has a substantial beneficial effect on sexual life and that time dedicated to explanation of disease as well as treatment support is associated with improved QoL in a very short time has been described before (33,36). These findings suggest a need for attention for possible genital psoriasis during the first consultation in daily clinical practice.…”
Section: Discussionmentioning
confidence: 73%
“…An explanation for this may be that the SQoL in men was not severely enough affected, so there was less room for improvement. The fact that clinical improvement has a substantial beneficial effect on sexual life and that time dedicated to explanation of disease as well as treatment support is associated with improved QoL in a very short time has been described before (33,36). These findings suggest a need for attention for possible genital psoriasis during the first consultation in daily clinical practice.…”
Section: Discussionmentioning
confidence: 73%
“…The improved quality of life may relate to obtaining a diagnosis, explanation, and treatment leading to clinical improvement of patients' vulvar disease. Time for explanation is an important factor in treating skin disease as shown in a Swedish study looking at quality of life before and after treatment at a dedicated dermatological outpatient treatment unit [3]. They showed a 57% reduction in DLQI scores after 6 weeks of intensive treatment and support from medical and nursing staff.…”
Section: Discussionmentioning
confidence: 97%
“…It has previously been demonstrated that regular outpatient treatment within a general dermatology setting, with time dedicated to explanation of disease as well as treatment, is associated with improved quality of life as measured by the Dermatology Life Quality Index (DLQI) [3].…”
mentioning
confidence: 99%
“…18 Impaired quality of life, which is common in people with chronic skin diseases, may not necessarily relate to disease severity. Therefore, this study included other factors that may be related to quality of life, such as social and demographic aspects.…”
Section: Discussionmentioning
confidence: 99%